Safety evaluation method of bottom coal thickness in thick coal seam roadway - Yunliang Tan; Shilin Song; Xiufeng Zhang; Xuesheng Liu (Scientific Reports)
Abstract In recent years, the number of roadway floor rock burst accidents is increasing, which seriously restricts the safe production of the mine. Therefore, safety evaluation method of bottom coal thickness in thick coal seam roadway was studied. The research results shown that the stress concentration area of composite floor is distributed in coal seam or rock stratum with large elastic modulus. With the increase of floor rock strength, the stress of coal-rock composite floor increased gradually, but the displacement and energy decreased gradually. When floor rock strength was equal to bottom coal strength, the increase of floor stress and displacement with the change of bottom coal thickness was the smallest, which was 34.29% and 33.61% respectively. The elastic strain energy decreased from 14.58 to 9.85%. With the increase of bottom coal thickness, the stress and displacement of coal-rock composite floor increased first and then decreased, and the elastic strain energy decreased gradually. It puts forward the safety evaluation method of bottom coal thickness: floor failure depth → reasonable thickness of bottom coal → safety thickness of bottom coal. It can provide reference for design of roadway bottom coal retention and surrounding rock control in thick coal seam face.